Nutrition Profile of the Destitute Women and Children in a Selected Rehabilitation Centre in Gazipur (Bangladesh Journal of Nutrition, 2015)
The present study attempts to identify the nutrition profile of the destitute women and children living in a rehabilitation center, Shishu Polli Plus (SPP), Gazipur. The vision of SPP is to serve underprivileged orphan children and destitute women and rehabilitate them by providing education and skill training. Information on anthropometric data, dietary intake, prevalence of morbidity and health and nutrition knowledge of SPP beneficiaries were collected by visiting the rehabilitation center. Dietary intake was calculated using dietary weighing of 7 consecutive days. Mean energy intake of SPP inmates was 1759 Kcal (86% of RDA). Mean intake of other nutrients were- protein 43 g, fat 33g, CHO 325g, calcium 307mg, iron 17mg, vitamin A 4120 IU, thiamine l.21mg, riboflavin 0.59mg and vitamin C 61 mg. They fulfilled the RDA for protein (96%), vitamin A (240%), and thiamine (ll8%). They were deficient in calcium (61% of RDA), iron (77% of RDA), riboflavin (48% of RDA) and vitamin C (130% of RDA; without considering cooking loss). Anthropometric assessments of the inmates indicated the presence of double burden of malnutrition at SPP. The great majority of the children (specially under-5) were undernourished; while at the same time about 9% of all adult women were found obese (BMI >25). Overall one in five children in SPP was found to be stunted. The situation however changes dramatically with age. A higher prevalence of stunting was reported with the lower age group of children. According to the weight for age and weight for height classification of nutritional status, about 30 per cent of all children residing at SPP were underweight and one quarter of all SPP children were, wasted. SPP environmental hygiene was much appreciated and the personal hygiene of SPP was far better than those of their counterparts in rural areas. The morbidity reporting was very few except for skin diseases. But SPP inmates' knowledge on nutrition and health was very poor. The study findings are encouraging in that the dietary intakes, anthropometry and the knowledge base (nutrition and health) of the SPP beneficiaries are comparable to those of their counterparts in the rural Bangladesh. This implies that without SPP interventions and attention the real life situation for these inmates would have been different. SPP has been trying very hard to bring meaningful changes in the life and living of these destitute.